2011
DOI: 10.1007/s11010-011-0865-7
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of HMGA1 expression by RNA interference suppresses growth of osteogenic sarcoma

Abstract: The expression of high mobility group protein A1 (HMGA1) protein has been closely related to various malignant and prognostic degrees of tumor. To investigate the influence of down-regulating HMGA1 on the tumor and the mechanism underlying antitumor of HMGA1, we transfected the HMGA1 shRNA vector into the osteogenic sarcoma MG-63 cell and observed the changes of cell proliferation, invasion abilities, and the tumor growth. HMGA1 gene expression could be efficiently inhibited, and cell proliferation, migration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…We verified the positive effects of HMGA1 on osteosarcoma cell proliferation, migration and invasion using RNA interference. Our result was similar to Yuan and colleagues' findings, who reported that silencing of HMGA1 was able to suppress osteosarcoma growth [30]. Moreover, the inhibitory effects exerted by miR-142-3p on proliferation, migration and invasion were reversed partially after HMGA1 overexpression.…”
Section: Discussionsupporting
confidence: 92%
“…We verified the positive effects of HMGA1 on osteosarcoma cell proliferation, migration and invasion using RNA interference. Our result was similar to Yuan and colleagues' findings, who reported that silencing of HMGA1 was able to suppress osteosarcoma growth [30]. Moreover, the inhibitory effects exerted by miR-142-3p on proliferation, migration and invasion were reversed partially after HMGA1 overexpression.…”
Section: Discussionsupporting
confidence: 92%
“…The present study also observed that a reduction in the expression of HMGA1 led to a reduced growth rate in H1299 cells. The suppression of cell growth in response to the suppressed expression of HMGA1 has also been observed in breast cancer and osteogenic sarcoma (26). …”
Section: Discussionmentioning
confidence: 92%
“…HMGA1 inhibits the function of p53 family members in thyroid cancer cells, increases the expression of oncogenic miR-222 in lung cancer cells, enhances cancer cell resistance to genotoxic agents, enhances epithelial-mesenchymal transition, and promotes tumor progression in breast cancer cells [25,[38][39][40]. Recent study has shown HMGA1 upregulation to be associated with survival in pancreatic ductal adenocarcinoma whereas downregulation of HMGA1 has enhanced gemcitabine chemosensitivity for suppressing growth of tumor cells [26,41,42]. Our study has showed that HMGA1 as an architectural transcription factor was expressed in gliomas but not expressed in normal human brain tissue, that HMGA1 expression in GM was higher than in WHO grade II and III gliomas, and that overexpression of HMGA1 was closely correlated with high levels of Ki67, MVD, VEGF-A, and MMP-9, which were related to tumor progression.…”
Section: Discussionmentioning
confidence: 99%